Contact tracing is associated with treatment success of index tuberculosis cases in Uganda. (August 2021) - Baluku, Joseph Baruch; Kabamooli, Rachael Alele; Kajumba, Norah; Nabwana, Martin; Kateete, David; Kiguli, Sarah; Andia-Biraro, Irene
Highlights: Tuberculosis (TB) contact tracing identifies undiagnosed TB in index TB case contacts We determined the effect of contact tracing on outcomes of index TB cases Contact tracing was associated with higher treatment success and cure It was also associated with lower death, loss to follow-up and treatment failure ABSTRACT: OBJECTIVE: To determine the effect of contact tracing on the treatment outcomes of index tuberculosis (TB) cases in Uganda. METHODS: We evaluated TB cases registered at an urban public health facility in Uganda in 2015–2020. We extracted data from the unit's TB and contact tracing registers. Treatment outcomes were classified as cure, loss to follow-up, death and treatment failure. Treatment success was the sum of cure and treatment completion. RESULTS: Among 778 TB cases, contact tracing was conducted for 455 (58.5%). Compared with cases without contract tracing (n=323), cases with contract tracing (n=455) had higher treatment success (92.5% vs 79.3%) and cure rates (57.1% vs 39.9%) and lower loss to follow-up (3.5% vs 9.3%), treatment failure (0.4% vs 1.6%) and death (3.5% vs 9.9%) ( P <0.001). Contact tracing was associated with higher odds of treatment success (adjusted odds ratio (aOR) 3.00, 95% CI 1.92–4.70, P <0.001) and cure (aOR 3.11, 95% CI 1.97–4.90, P <0.001), and lower odds of loss to follow-up (aOR 0.33, (0.13–0.83), P =0.018) and death (aOR 0.38, (0.20–0.72), P =0.003). CONCLUSION: TB contact tracing should be conducted consistently not only for the benefit of identifying new TB cases but also to promote treatment success of index cases.